Reformasi Struktur Perdagangan Internasional dalam WTO: Perspektif Joseph E. Stiglitz - Sasmita, Sulastri (Universitas Muhammadiyah Yogyakarta, 2015)
This article tries to explain about the institution of international political economy, especially the WTO as a multilateral trade organization that has created unequal relationship between the developed and the developing countries. WTO as the only international trade organization should be able to create a fair global trade flows and balance among its member countries. But in fact, the WTO actually deepen the gap between developed and developing countries. Many of agreement that born from WTO are not implement as expectation. The implementation of WTO’s agreement just make developing countries more suffer. This resulted in the emergence of criticism from developing countries and one of the globalization’s figure, especially transformasionalist-globalist i.e Joseph E. Stiglitz. Seeing the reality of injustice in WTO, Stiglitz then argued for reforms the structure and system inside of WTO, so it can be an institution of fair trade and friendly to the developing countries.